Temporary immutability: A removable blockchain solution for prosumer-side energy trading. (15th April 2021) - Dorri, Ali; Luo, Fengji; Karumba, Samuel; Kanhere, Salil; Jurdak, Raja; Dong, Zhao Yang
Abstract: Recently, blockchain adoption in prosumer-side energy trading has been actively studied. However, most of the conventional frameworks permanently store all transactions which increases blockchain management cost and reduces the user privacy. Additionally, most of the existing solutions focus on facilitating energy trading and negotiation, while ignoring two critical issues: data acquisition and contract execution. The former refers to the process of collecting power generation/consumption information from on-site energy resources which is required to scale. The latter refers to the process of adjusting controllable loads' operation in real-time. In this paper, we propose a removable blockchain architecture that introduces a Temporary Chain (TC) where transactions can be stored for a particular period of time. The architecture enables an energy manager node to effectively collect data for facilitating real-time load control. TC reduces the volume of transactions stored in blockchain which increases scalability, throughput, and privacy of the users and reduces latency. We present two approaches to implement TC which are: i) blackboard where a central authority stores temporary transactions, and ii) removable ledger. We introduce a lightweight mode to transfer data. The implementation results show that the proposed framework reduces blockchain storage size and delay and increases throughput.